Hypoxia favors myosin heavy chain beta gene expression in an Hif-1alpha-dependent manner - Binó, Lucia; Procházková, Jiřina; Radaszkiewicz, Katarzyna; Kučera, Jan; Kudová, Jana; Pacherník, Jiří; Kubala, Lukáš (Oncotarget, 2017)
The potentiation of the naturally limited regenerative capacity of the heart is dependent on an understanding of the mechanisms that are activated in response to pathological conditions such as hypoxia. Under these conditions, the expression of genes suggested to support cardiomyocyte survival and heart adaptation is triggered. Particularly important are changes in the expression of myosin heavy chain (MHC) isoforms. We propose here that alterations in the expression profiles of MHC genes are induced in response to hypoxia and are primarily mediated by hypoxia inducible factor (HIF). In in vitro models of mouse embryonic stem cell-derived cardiomyocytes, we showed that hypoxia (1% O2) or the pharmacological stabilization of HIFs significantly increased MHCbeta (Myh7) gene expression. The key role of HIF-1alpha is supported by the absence of these effects in HIF-1alpha-deficient cells, even in the presence of HIF-2alpha. Interestingly, ChIP analysis did not confirm the direct interaction of HIF-1alpha with putative HIF response elements predicted in the MHCalpha and beta encoding DNA region. Further analyses showed the significant effect of the mTOR signaling inhibitor rapamycin in inducing Myh7 expression and a hypoxia-triggered reduction in the levels of antisense RNA transcripts associated with the Myh7 gene locus. Overall, the recognized and important role of HIF in the regulation of heart regenerative processes could be highly significant for the development of novel therapeutic interventions in heart failure.